Associations between APOE-, COMT Val108/158Met- and BDNF Val66Met polymorphisms and variations in depressive and anxiety symptoms, sense of coherence and vital exhaustion in the real-life setting of mandatory basic military training - Alexopoulos, Panagiotis; Papanastasiou, Anastasios D.; Εconomou, Polychronis; Beis, Pavlos; Niforas, Michail; Dassios, Theodore G.; Kormpaki, Aggeliki; Zarkadis, Ioannis K.; Reichel, Martin; Kornhuber, Johannes; Perneczky, Robert; Gourzis, Philippos (Journal of Neural Transmission, 2021)
Apolipoprotein E (APOE) ε, catechol-O-methytranferase (COMT) Val108/158Met and brain-derived neurotrophic factor (BDNF) Val66Met single nucleotide polymorphisms (SNPs) were shown to affect stress perception and response. The present study explored possible associations between these SNPs and changes in subclinical anxiety- and depressive symptoms, sense of coherence (SOC) and vital exhaustion (VE) during compulsory basic military training. The study encompassed 179 conscripts of a training base in Greece. The neuropsychiatric assessment was based on the Beck Depression Inventory, the State-Trait Anxiety Inventory, the Antonovsky SOC scale and the Maastricht Questionnaire. It was conducted at three time points of the 19-day basic military training: on day one (baseline), day six (follow-up I) and day 13 (follow-up II). Statistical analyses included Mann–Whitney test, Chi-square test and cross-sectional time series regression models based on the Skillings–Mack statistic. APOE ε4 non-carriers encountered significant changes in anxiety- and depressive symptoms and SOC (in all cases P < 0.001) over the observation period, whilst ε4 carriers did not. The changes in anxiety, depressive symptoms and SOC attained statistical significance in both BDNF Met66 carriers (in all cases P < 0.001) and non-carriers (P = 0.036; < 0.001; < 0.001, respectively) as well as in COMT Met108/158 carriers (P = 0.004; < 0.001; < 0.001, respectively) and non-carriers (P = 0.02; 0.01; 0.021, respectively. Changes over time in VE were not significant (P > 0.05). The observed resistance of APOE ε4 carriers vs non-carriers to changes in anxiety- and depressive symptoms and SOC when exposed to a stressful environment may point to superior coping capacities of healthy young men carrying the ε4 allele.
CRIS-Team Scopus Importer:2021-01-15
Keywords: BDNFVal66Met; COMT Val108/158Met; Sense of coherence; Subclinical depressive and anxiety symptoms; Vital exhaustion